2006
DOI: 10.1021/la0602214
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Surface Reactivity of Ferrihydrite Nanoparticles Assembled in Ferritin

Abstract: Ferrihydrite nanoparticles with nominal sizes of 3 and 6 nm were assembled within ferritin, an iron storage protein. The crystallinity and structure of the nanoparticles (after removal of the protein shell) were evaluated by high-resolution transmission electron microscopy (HRTEM), atomic force microscopy (AFM), and scanning tunneling microscopy (STM). HRTEM showed that amorphous and crystalline nanoparticles were copresent, and the degree of crystallinity improved with increasing size of the particles. The do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
39
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 55 publications
8
39
2
Order By: Relevance
“…These electron transfer rates are greater than the Mössbauer nuclei decay rate of 7.1×10 6 s −1 which means a localized Fe(II) signal will not be observed. The previously observed formation of a localized 57 Fe(II) in 57 ferrihydrite after 56 Fe(II) sorption is consistent with the lower conductivity of ferrihydrite (band gap up to 2.7 eV [24]) relative to hematite (band gap 2.2 eV [25]). …”
Section: Resultssupporting
confidence: 80%
“…These electron transfer rates are greater than the Mössbauer nuclei decay rate of 7.1×10 6 s −1 which means a localized Fe(II) signal will not be observed. The previously observed formation of a localized 57 Fe(II) in 57 ferrihydrite after 56 Fe(II) sorption is consistent with the lower conductivity of ferrihydrite (band gap up to 2.7 eV [24]) relative to hematite (band gap 2.2 eV [25]). …”
Section: Resultssupporting
confidence: 80%
“…Since the metal content was considerably higher in case of holoferritin (2660 Fe atoms) compared to the reconstituted ferritins ($300-550 metal atoms), while still the current obtained from holoferritin was less than that obtained from the Co(III)-ferritin and Cu(II)-ferritin, it follows that the extent of metal loading did not directly influence the order of the conductivities of the five ferritin systems. Liu et al also showed earlier that the extent of iron loading in apoferritin did not directly correlate with its conductivity [39]. For further verification, we examined a Fe(III)-ferritin system where the Fe atoms were incorporated into the apoferritin cavity in a controlled manner, so that the iron content, which was found to be 750 from ICP measurements, was comparable to the metal contents in other reconstituted ferritins.…”
Section: Role Of Metal Content In Observed Band Gap Disparities Amongmentioning
confidence: 83%
“…The two structural forms of free ferrihydrite often studied are the smaller, less-ordered two-line (2L) ferrihydrite and the larger, more-ordered six-line (6L) ferrihydrite, where the number of lines refers to the number of X-ray diffraction maxima [25, 26]. When the iron content per ferritin protein cage is lower, the ferritin mineral resembles 2L ferrihydrite; as the iron content per cage increases, the mineral resembles 6L ferrihydrite [27, 28]. We compared free 2L and 6L ferrihydrite with 2L and 6L ferrihydrite inside ferritin cages for three reasons: (1) structurally distinct, microscale to macroscale iron (oxyhydr)oxide minerals have in the past influenced bacterial iron bioavailability [17, 2931] and dissolution rates in the presence of siderophores [32]; (2) aggregation of free ferrihydrite [15–17] is faster with 2L ferrihydrite than with 6L ferrihydrite (unpublished observations); (3) ferritin protein cages, which control both mineral synthesis and dissolution [23, 24, 33], may be degraded in diseased tissue [34, 35], exposing the ferrihydrite core (hemosiderin).…”
Section: Introductionmentioning
confidence: 99%